Diagnostic Engineering Applied to Property Appraisal: Contributions to Depreciation Calculation - Barbosa, Larissa Kelly da Silva França; Monteiro, Eliana Cristina Barreto; Lago, Eliane Maria Gorga; Florencio, Lutemberg de Araújo; Cruz, Felipe Mendes da (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the impact of building pathologies on the depreciation of urban properties and to propose the adaptation of the Ross-Heidecke method to the Brazilian context, aiming to reduce the subjectivity of traditional calculations and increase the reliability of appraisal reports.Methodology – A conceptual and comparative approach was adopted, including a review of depreciation methods used in Brazil and their practical application to a 22-year-old multifamily residential building. The inspection covered common areas and housing units, following the criteria of NBR 15575 and technical protocols for building inspection.Originality/Relevance – The study is original in integrating building diagnostics with property appraisal by incorporating the diagnosis of pathological manifestations as a criterion for defining the depreciation coefficient. This proposal addresses the gap in methods that consider only age and service life, providing greater accuracy in the calculation.Results – A significant variation among the methods analyzed was observed, with depreciation coefficients ranging from 9.88% to 35.02%. The adapted Ross-Heidecke model showed greater potential to represent the real conservation condition of the property, reducing the dispersion of results.Theoretical/Methodological Contributions – The study enhances the technical rigor of depreciation calculations, uses NBR 15575 as a performance benchmark, and suggests a checklist based on pathological anomalies applicable to building inspections.Social and Environmental Contributions – The research contributes to more accurate diagnoses, promotes the valorization of well-maintained buildings, stimulates a culture of preventive maintenance, and provides greater transparency in real estate transactions. Furthermore, it strengthens legal security and supports urban sustainability by encouraging conservation practices.
Keywords: Real estate depreciation; Building pathologies; Urban property appraisal